CREditing: a tool for gene tuning in Trypanosoma cruzi (2020)
The genetic manipulation of Trypanosoma cruzi continues to be a challenge, mainly due to the lack of available and efficient molecular tools. The CRE-lox recombination system is a site-specific recombinase technology, widely used method of achieving conditional targeted deletions, inversions, insertions, gene activation, translocation, and other modifications in chromosomal or episomal DNA. In the present study, the CRE-lox system was adapted to expand the current genetic toolbox for this hard-to-manipulate parasite. For this, evaluations of whether direct protein delivery of CRE recombinase through electroporation could improve CRE-mediated recombination in T. cruzi were performed. CRE recombinase was fused to the C-terminus of T. cruzi histone H2B, which carries the nuclear localization signal and is expressed in the prokaryotic system. The fusion protein was affinity purified and directly introduced into epimastigotes and tissue culture-derived trypomastigotes. This enabled the control of gene expression as demonstrated by turning on a tdTomato (tandem dimer fluorescent protein) reporter gene that had been previously transfected into parasites, achieving CRE-mediated recombination in up to 85% of parasites. This system was further tested for its ability to turn off gene expression, remove selectable markers integrated into the genome, and conditionally knock down the nitroreductase gene, which is involved in drug resistance. Additionally, CREditing also enabled the control of gene expression in tissue culture trypomastigotes, which are more difficult to transfect than epimastigotes. The considerable advances in genomic manipulation of T. cruzi shown in this study can be used by others to aid in the greater understanding of this parasite through gain- or loss-of function approaches.